Kenézy Gyula a Debreceni Egyetem első orvos-rektora - Lampé, László (Gerundium, 2014)
GYULA KENÉZY, THE FIRST PHYSICIAN RECTOR OF THE UNIVERSITY OF DEBRECEN. Gyula Kenézy, the Medical Officer of the free royal city of Debrecen and the Director of the Midwife Training Institution was the the motivation behind the movement with the aim to establish the third whole university in Hungary in Debrecen with a medical faculty. Without his work, there would have not been a university in Debrecen for a long time. After the establishment of the university, he was appointed as the Commissioner of the construction and as the irst obstetrician professor. Based on his unquestionable merits, he had received the post of the Rector from the Medical Faculty. In his former residence a museum named after him was established.